ABOUT COMMON AND THEORETICAL INFORMATICS - Andrey A. Mayorov; Vladimir P. Sedyakin (Открытое образование (Москва), 2016)
In this article are considered the integrant importance of informatics and informational technologys includes the sciences and the humanities.There are a differences between scientifi c grounds of the various information orientations, which include physical informatics, bioinfomatics, technical and social informatics. Creation of a united theoretical base for these orientations is very problematical. The metodologically important issue of classifi cation different informatics is a part of the general informatics, the example of which are considered here.